A Novel IoT-as-a-Service Strategy to Achieve Energy and Cost Saving In Microgrids - Giacobbe, Maurizio; Puliafito, Antonio; Scarpa, Marco; Gabriella Xibilia, Maria (International Journal of Engineering and Technology, 2018)
Smart Grids play a crucial role for always more efficient, flexible and reliable integration of technologies in the electricity marketplace. At the “edge” of Smart Grids, appliances and consumer devices consume electricity by Microgrids. End-users need easily and dynamically accessible electricity marketplace and heterogeneous renewable energy sources (e.g., solar, wind, etc.), in order to satisfy energy needs. This implies two main challenges: 1) managing the variable availability of renewables, mainly due both to variable electricity marketplace conditions and to a not-continuous energy sourcing; 2) managing the energy supply/demand ratio especially in presence of scarcity or surplus conditions in the electrical energy providing service. In this paper the authors propose a novel two-levels Internet of Things-as-a-Service (IoTaaS) strategy to “win” the above-mentioned challenges.